Facilitated physiological adaptation to prolonged circadian disruption through dietary supplementation with essence of chicken. (26th November 2015) - Wu, Tao; Yao, Cencen; Tsang, Fai; Huang, Liangfeng; Zhang, Wanjing; Jiang, Jianguo; Mao, Youxiang; Shao, Yujian; Kong, Boda; Singh, Paramjeet; Fu, Zhengwei
Abstract : Synchrony between circadian and metabolic processes is critical to the maintenance of energy homeostasis. Studies on essence of chicken (EC), a chicken meat extract rich in proteins, amino acids and peptides, showed its effectiveness in alleviating fatigue and promoting metabolism. A recent study revealed that it facilitated the re-entrainment of clock genes ( Bmal1, Cry1, Dec1, Per1 and Per2 ) in the pineal gland and liver in a rat model of circadian disruption. Here, we investigated the role of EC-facilitated circadian synchrony in the maintenance of the energy homeostasis using a mouse model of prolonged circadian disruption. Prolonged circadian disruption (12 weeks) resulted in hepatic maladaptation, manifested by a mild but significant ( p < 0.05) hepatomegaly, accompanied by disturbed hepatic lipid metabolism and liver injury (indicated by increased circulating hepatic enzymes). Evidently, there was marked elevations of hepatic inflammatory mediators (interleukin-1beta and interleukin-6), suggesting an underlying inflammation leading to the hepatic injury and functional impairment. Importantly, the disruption paradigm caused the decoupling between key metabolic regulators (e.g. mTOR and AMPK) and hepatic clock genes ( Per1, Cry1, Dec1, Bmal1 ). Further, we showed that the loss of circadian synchrony between the master and hepatic clock genes ( Per1, Cry1, Dec1, Bmal1 ) could be the underlying cause of the maladaptation. When supplemented with EC, the functional impairment and inflammation were abolished. The protective effects could be linked to its effectiveness in maintaining the synchrony between the master and hepatic clocks, and the resultant improved coupling of the circadian oscillators ( Per1, Cry1, Dec1, Bmal1 ) and metabolic regulators (mTOR, AMPK). Overall, EC supplementation promoted the physiological adaptation to the prolonged circadian disruption through facilitation of endogenous circadian synchrony and the coupling of circadian oscillators and metabolic regulators. This forms an important basis for further elucidation of the physiological benefits of EC-facilitated circadian synchrony.